A new high activity plasma cholinesterase variant. Issue 10 (October 1988) - Krause, A; Lane, A B; Jenkins, T
Abstract : A South African Afrikaans speaking family is reported in which a new high activity plasma cholinesterase variant was found to occur in the mother and son. The variant has the same electrophoretic mobility as the "usual' enzyme, but greater heat stability. Its higher specific activity is associated with a normal number of enzyme molecules. The variant may be inherited as a dominant trait, though its locus is uncertain.